Упругие колебания трехслойных пластин с покрытыми диафрагмой торцами - Алтухов, Е.В.; Фоменко, М.В. (Прикладная механика, 2014)
Дано розв‘язок тривимірної задачі про усталені коливання тришарових ізотропних пластин з покритими діафрагмою плоскими гранями. На межі поділу шарів прийнято умови ідеального контакту. Отримано однорідні розв’язки системи рівнянь руху в переміщеннях. Проведено асимптотичний аналіз і чисельне дослідження дисперсійних рівнянь. Наведено діаграми спектральних кривих, графіки змін фазових і групових швидкостей. The three-dimensional problem about the steady-state vibrations of threelayered isotropic plates with flat faces covered by a diaphragm is considered. Conditions of ideal contact are satisfied on interface of layers. The homogeneous solutions of equations system of motion in the displacements are got. The asymptotic analysis and computational investigations of dispersive equations are carried out. Diagrams of spectral curves, change curves of phase and group velocities are represented.